2018
DOI: 10.20450/mjcce.2018.1503
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel isocoumarin derived polymer and its thermal decomposition kinetics

Abstract: A novel isocumarin derived polymer poly(2-(isocoumarin-3-yl)-2-oxoethyl methacrylate) poly(ICEMA) was synthesized by free radical polymerization. The spectral characterization was performed with FTIR and 1H,13C-NMR techniques. The glass transition temperature of poly(ICEMA) was measured to be 161.69 °C by DSC technique. The initial decomposition temperatures obtained from TGA showed a change in the positive direction from 256.59 °C to 286.10 °C as the heating rate increased to 20 °C/min. Thermal decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The linearity for this line was found to be R 2 = 0.994. The activation energies of both the Kissinger and Flynn-Wall-Ozawa methods are very similar, with only a 7.3 kJ/mol difference between them, thereby illustrating the reliability of the results [16,17,29]. The thermal degradation mechanism of the bithiazole-containing conjugated polymer was determined when the activation energies calculated from the various kinetic methods in the literature were compared with the activation energies obtained from the Flynn-Wall-Ozawa and Kissinger methods.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The linearity for this line was found to be R 2 = 0.994. The activation energies of both the Kissinger and Flynn-Wall-Ozawa methods are very similar, with only a 7.3 kJ/mol difference between them, thereby illustrating the reliability of the results [16,17,29]. The thermal degradation mechanism of the bithiazole-containing conjugated polymer was determined when the activation energies calculated from the various kinetic methods in the literature were compared with the activation energies obtained from the Flynn-Wall-Ozawa and Kissinger methods.…”
Section: Resultsmentioning
confidence: 74%
“…The closest value to the calculated average activation energy value was obtained with the value corresponding to 288.5 kJ/mol at the conversion of 11 %. An increase in the activation energy values was also observed depending on the increase in the percentages of decomposition [16][17][18]29]. In order to evaluate the thermal degradation kinetics of the bithiazole-containing conjugated polymer, the Kissinger method, another kinetic method independent of reaction order, was used to support and confirm the thermal degradation activation energies calculated from the Flynn-Wall-Ozawa method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results for thermal degradation of heterocyclic polymers have been reported in our previous publications and also by different researchers. [34][35][36][37][38][39][40][41][42] For example, Kurt et al 37 reported the degradation temperatures of an isocoumarin derived polymer changed in a positive direction, which increased 256.6 °C to 286.1 °C by increasing heating rate from 5 to 20 °C/min. Meng and friends investigated the thermal degradation kinetics of a polyimide polymer containing 2,6-benzobisoxwwwwazole units and reported the onset decomposition temperatures increased with increase of heating rates.…”
Section: Resultsmentioning
confidence: 99%
“…The structurally diverse isocoumarin derivatives X(1–20) were synthesised according to the general synthetic route shown in Scheme 1 . 3-Acetylisocoumarin-substituted compounds B were synthesised as previously described by some of us 15 . The hydrazone derivatives X(1–5) were obtained by reacting B with substituted hydrazines 16 .…”
Section: Resultsmentioning
confidence: 99%